David Patrikarakos, War in 140 Characters: How Social Media is reshaping Conflict in the Twenty-First Century - Mr. Saadain Gardezi (CISS Insight Journal, 2020)
David Patrikarakos is a British journalist, author and TV producer. He is the author of Nuclear Iran: Birth of an Atomic State, a contributing editor at the Daily Beast, and a contributing writer at Politico, Foreign Policy and several other publications. War in 140 Characters explains the changing nature of conflict after the inception of social media. The book contains accounts of several individuals and networks, that became significant actors in 21st century conflicts. It also elaborates how the Clausewitzian idea of war has become less relevant, as apart from the physical dimension, war has become a clash of narratives on a virtual battlefield as well. The author has relied on his own reporting from war zones and on firsthand interviews with important players in different conflicts, as primary sources to support his findings.